Analysis of Internal and External Faults Occur in the High Voltage Power Grid (Aintelia Science Notes, 2022)
Electrical energy is among the most important needs of individual and corporate life with its widespread use. In today's conditions, where economic competition is intensified, both for consumers and for the generation, transmission and distribution units that make up the power system, even a short-term interruption in electrical energy brings along many problems. Therefore, considering the energy transmission lines, which are one of the basic operating structures of the power system, a fault should be eliminated as soon as possible. In this study, fault current levels and their causes; Common faults such as electrical causes, mechanical causes, natural causes, faulty maneuvers, overheating, punctures, disconnector and breaker failures, forces at busbar connection points, damages in networks, transformer failures are analyzed in terms of their sources and structures, and solution methods are proposed. In addition, the mentioned cases are also examined in terms of internal over-voltages, external overvoltages and voltage drop-induced faults.